Evolution of lakes near the Dzhikiugankez glacier (Northern Elbrus area) in 1957–2020 with consideration of underground flow channels - M. Dokukin D.; E. Savernyuk A.; M. Bekkiev Yu.; R. Kalov Kh.; A. Khatkutov V.; М. Докукин Д.; Е. Савернюк А.; М. Беккиев Ю.; Р. Калов Х.; А. Хаткутов В. (Ice and Snow, 2022)
Evolution of lakes near the Dzhikiugankez Glacier in the north of Elbrus for the period of 1957–2020 was studied using a comparative interpretation of aerial and satellite images as well as aerial and ground surveys in 2007–2018. Within this period the area of the Dzhikiugankez Glacier (43,35 N, 42,53 E) decreased by 8.2 km2. On the territory previously occupied by the glacier and close to it, 19 lakes appeared at different times, which dynamically developed and broke through. The lakes cover the area of 0.43 km2, that equals to 5.21% of the total icefree area. The average area of the lakes is 26.6 thousand m2. The maximum (the lake East Birdzhaly) is 89 thousand m2. In total there were six lakes larger than 25 thousand m2. They are concentrated in depressions on the surface of an ancient lava flow dammed by glaciers, dead ices and moraine lines. At a certain stage in the evolution of lakes, water from them penetrated through these barriers and, thus, formed subglacial and underground drainage channels. In 2013, during helicopter flights, an underground drainage channel with a length of more than 80 m was detected in the moraine line around the Lake «Podkova». The survey made possible to determine decreasing in the lake level by 2 m, and the accumulation of water with a volume of up to 48 thousand m3 in the cavities of the moraine massif, until it reaches the outer slope. The accumulated volume of water interflowed through the underground channel gradually, but despite the pot-holes on its bottom, no mudflow happened in the valley. Although in another case, the formation of an underground drainage channel from the Severnoye Chungurchat Lake was accompanied by a lake breakthrough and a mudflow. Other characteristic features of the evolution of lakes and changes in the direction of drainage from glaciers are also analyzed in the paper. По данным дешифрирования аэрофотоснимков и космических снимков за 1957–2020 гг., а также полевых наблюдений и вертолётных облётов определены особенности эволюции озёр у ледника ...